Reduction of the net income as a function of deficit and excess of water on beans - Paz, Vital Pedro da Silva; Frizzone, José Antonio; Botrel, Tarlei Arriel; Folegatti, Marcos Vinicius (Pesquisa Agropecuaria Brasileira, 1997)
The adequate management of irrigation systems has to provide the farm the efficient water use, increasing yield crop, decreasing costs and maximizing the benefits. The objective of this work was to analyze the effect of product price, water cost and water distribution uniformity on the net income of beans crop. Christiansen's water uniformity coefficient was used. The data analysis allowed to conclude: 1) irrigation systems that do not have a high water uniformity distribution are not adequate when the objective is to reach the maximum net income; 2) if the crop has a high value, a high water uniformity distribution should be expected in order to decrease the water deficit effect on the net income; 3) the best economic results with any combination of product and water cost is observed under high irrigation uniformity; 4) when land availability is restrictive for total yield, beans price reduction has a greater influence on net income compared to increasing water cost.